Desempenho De Municípios Brasileiros em Relação à Estratégia de Investimento Público em Educação - Elisandra Henn Diel (Desenvolvimento em Questão, 2014)
The aim of this study was to analyze the performance of municipalities with over 100 thousand inhabitants, related to their strategy of public investment in education. This study is justified by the importance of the education for social and economic development of the country and by the necessity of follow-up the allocation of public resources. The method used was the data envelopment analysis (DEA). The input was the amount spending on education, and the outputs were number of students enrolled in schools by total of residents, the number of teachers, the number of schools, and average grades. The research is characterize as descriptive, documentary and quantitative. As conclusion, the group with higher efficiency is the group 5, which presented three cities with Score 1; the cities of Campinas – SP, Belém – PA and Salvador – BA, are consider 100% efficient in allocation of resources in education. The group 5 had most municipalities with efficient resource allocation in more than 50%, for 12 municipalities among the total sample, which corresponds to 85.7% of the municipalities. Between these 12 municipalities, 10 are state capitals. The other groups have one single city with 100% utilization of resource, each of them.